An annotated catalog of the Iranian Reduvioidea (Hemiptera: Heteroptera: Cimicomorpha) - Ghahari, Hassan; Moulet, Pierre; Cai, Wanzhi; Karimi, Javad (Zootaxa, 2013)
An updated list of Iranian Reduvioidea Latreille (families Pachynomidae, Reduviidae) is presented and discussed in this paper. For Iranian fauna, there are records of one species of Pachynomidae and 109 species and subspecies of assassin bugs (Reduviidae) distributed in 24 genera and subgenera, and seven subfamilies, Emesinae, Harpactorinae, Holoptilinae, Peiratinae, Phymatinae, Reduviinae, and Stenopodainae. We report 6 new country records and one new species, Empicoris baerensprungi (Dohrn, 1863) for Asian fauna. Synonyms and distribution data are also given.